Gut microbiota in professional and amateur athletes: the impact of physical activity on microbiota - what do we know? A literature review - Szopa, Sebastian; Szymonik, Julia (Quality in Sport, 2024)
Introduction and purpose: The gut microbiota, a diverse community of microorganisms inhabiting our intestines, is pivotal for human health. This intricate microbial ecosystem influences various aspects of health, including digestion, metabolism, immune function and even mental well-being. Comprehending connections between physical activity and gut microbiota is vital for public health advocacy, particularly amidst the rise of sedentary lifestyle. The nature of modern lifestyles contributes to decreased physical activity, exacerbating the health consequences associated with a disrupted gut microbiota. In conditions such as type 2 diabetes, hypertension, and obesity, alterations in the composition and function of the gut microbiota have been observed. These changes, often referred to as dysbiosis, are characterized by a decrease in microbial diversity and shifts in the relative abundance of certain bacterial taxa. The aim of this study is to provide a comprehensive overview of the current state of knowledge regarding the impact of professional and amateur physical activity on gut microbiota. Description of the state of knowledge: Recent research reveals a significant link between physical activity and the gut microbiota, hinting at its potential health implications. Studies indicate that exercise may promote greater microbial diversity in the gut, contributing to improved metabolic balance and reduced inflammation. Summary: Exercise can modulate the composition and diversity of gut microbes, promoting a more beneficial profile associated with enhanced metabolic health and immune function. Ongoing research in this area could guide the development of exercise plans that enhance not just physical fitness but also gut health and overall well-being.